Performance assessment of rotating spiral-shaped baffles built-in solar air heater: 4E and sustainability analysis - Yogeshkumar Khimsuriya; D.K. Patel; Vivek Patel; Vinay Pandit; Hashim Sahar Mohaisen; Lav Kumar Kaushik; Pranav Mehta; Himesh Patel (Case Studies in Thermal Engineering)
Solar air heaters (SAHs) often face efficiency limitations due to heat transfer challenges. Integrating roughness elements on the absorber plate is a common strategy, but stationary roughness induces hot spots and thermal wake zones, hindering convective heat transfer. To mitigate these issues, this study investigates a modified SAH with novel rotating spiral-shaped baffles using a 4E framework—energy, exergy, exergoeconomic, and enviroeconomic perspectives. Results demonstrate superior performance, with configurations at P/e = 8 and e/H = 0.8 achieving peak useful heat gains of 156.78 W. The modified SAH attains daily average thermal, exergy, and thermohydraulic efficiencies of 29.55 %, 14.59 %, and 7.24 %, respectively. Exergoeconomic analysis yields a maximum parameter of 0.36 kWh/$ over 30 years, while enviroeconomic assessments indicate a reduction in CO2 emissions from 17.14 to 5.71 kg/year, with carbon credit earnings between $102.86 and $308.57. Future research can further enhance performance through novel storage media, optimized baffle design, intelligent controls, and advanced heat exchangers.